Maintenance management system for Nirvana Memorial Park,Kulai [electronic resource] - Teo, Pei Ling, 1988-, author 638833 (2012)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2012